The Verbal Aggression in Relation to Social Compatibility among Children during Wars ’’ a Field Study applied at LATTAKIA City’’ - حاتم عبير (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The present study aimed to define the relationship of verbal aggression with social compatibility during wars among a sample of children ((immigrants ’scores and residents) in Lattakia. Are there differences of expatriates, residents, in both social harmony and verbal violence? And that is according to the gender variable (males and females). To achieve the objectives of the study, a questionnaire of verbal aggression and a questionnaire on the social compatibility of children were used. The study was conducted during the 2019-2020 academic year. The study adopted the descriptive approach. The study sample consisted of (299) children, (135) children from the Lattakia governorate, and (164) children coming to it from other governorates during the wartime. The researcher has applied the descriptive research method. The study was conducted between 2019-2020. For the sake of the research, the researcher attempted to verify five hypotheses, and consequently reached the following conclusions: There is a statistically significant relationship between the scores of the study sample individuals on the study variables (social compatibility, verbal aggression). There was no statistically significant difference between the averages (immigrants ’scores, and residents’ scores) on the social compatibility questionnaire. There was no statistically significant difference between the averages (immigrants ’scores, and residents’ scores) on the verbal aggression questionnaire. The existence of a statistically significant difference between the mean (male scores, and female scores) on the questionnaire of social compatibility.There was no statistically significant difference between the averages (male scores and female scores) on the verbal aggression questionnaire.